Design of a Dual-Band PIFA for Handset Devices and it SAR Evaluation - Pimienta-Del Valle, Domingo; Lagar-Pérez, Raidel (Ingeniería Investigación y Tecnología, 2016)
PIFA antenna (Planar Inverted F Antenna) is one of the most used in mobile devices, fundamentally for it reduced size. Because of the convergence of wireless services in one mobile device, it is convenient that it can operate in different frequencies, leading to multiband antenna design. Nonetheless, besides technical consideration, it is necessary the evaluation of antenna radiation impact in the user. Therefore, in this work a dual-band PIFA antenna for GSM 900 and GSM 1800 is presented and its interaction with a model of user hand and head is analyzed and evaluated by means of SAR (Specific Absorption Rate) parameter in a simulated manner. The dual-band characteristic is obtained by means of an insertion of an L-shaped slot, which will use to tune the operation frequencies.